Peran Kepemimpinan Diri dalam Meningkatkan Kemandirian dan Prestasi Akademik Mahasiswa di Lingkungan Kampus - Grace Yulianti; A Sigit Hadi Pramono; Eka Wahyu Kasih (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to explore the role of self-leadership in improving students' independence and academic achievement in the campus environment. The method used is a literature study by analyzing various literature related to the concept of self-leadership, its development strategies, and its impact on academic and non-academic aspects. The results of the study indicate that self-leadership contributes positively to students' ability to manage time, set goals, increase motivation, and develop independent learning habits through techniques such as goal setting, self-reward, and positive self-talk. In addition, the development of self-leadership skills has been shown to be an important foundation in forming students' attitudes of responsibility, self-confidence, and resilience in dealing with academic pressure. These skills also have an impact on improving students' achievement and readiness to face future challenges. This study provides recommendations for educational institutions to systematically integrate self-leadership training into the curriculum to support the development of students' character, independence, and career readiness in a sustainable manner.